Pengaruh Peran Kelompok Tani Terhadap Produktivitas Usahatani Padi di Desa Karanganom, Kecamatan Weleri, Kabupaten Kendal - Permatasari, Yesa; Mariyono, Joko; Dalmiyatun, Tutik (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Farmer groups that actively role as vehicles for learning, vehicles for cooperation, and production units play a significant role in enhancing agricultural output through efficient management practices and the adoption of innovations. An increase in production serves as a key indicator for improving the productivity of farming enterprises. This research aims to analyze the influence of farmer group roles comprising vehicles for learning, vehicles for cooperation, and production units along with farmer characteristics including age, education, farming experience, and land tenure status, on the productivity of rice farming. The research was conducted from February to April 2025 in Karanganom Village, Weleri Subdistrict, Kendal Regency, employing a survey method. Sampling was carried out using a purposive sampling technique. Data were analyzed using quantitative descriptive statistics and multiple linear regression analysis with SPSS Statistics 27. The results of the research indicate that all variables collectively have a significant effect on rice farm productivity, suggesting that simultaneous changes in these variables can either enhance or reduce productivity. Partially, the variables of vehicles for learning, production unit, age, education, farming experience, and land status were found to significantly influence productivity, whereas the vehicles for cooperation variable did not exhibit a significant partial effect. Among these, the production unit variable demonstrated the most dominant partial influence, highlighting the critical role of improving and expanding production units in positively driving rice farm productivity.